The relationships of color to performance and carcass traits in cattle - K.M. Andries; R.R. Schalles; D.E. Franke; Michael E. Dikeman (Kansas Agricultural Experiment Station Research Reports, 1993)
The effects of primary color (black, red, or white) on performance and carcass characteristics of 253 cross-bred calves were evaluated. The only effect of color was that white calves had lighter birth weights than red calves, which was probably the result of the maternal influence of the Brahman breed. White calves also had a lower carcass yield grade than red calves. No other effects of color on performance or carcass traits were found. It can be concluded that knowledge of breed and expected progeny differences (EPD) of the sire within the breed are more accurate methods of predicting the future performance and carcass characteristics of calves than color.
Keywords: Cattlemen& #x27; s Day; 1993; Kansas Agricultural Experiment Station contribution; no. 93-318-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 678; Beef; Cattle color; Performance; Carcass